Analyzing the Impact of Transmission Strategies on Localization Performance in Wireless Sensor Networks - Turan, Ismail Hakki; Yildiz, Dogan; Demirci, Sercan; Sayit, Muge (IEEE access, 2025)
Localization, essential in WSN applications, enables sensor nodes to determine their physical positions by referencing anchor nodes. We evaluate broadcast and unicast packet transmissions at the data-link layer for their impact on localization performance. Implemented on the Contiki-NG operating system, the study examines how anchor node density and antenna range affect localization success and the number of required anchor nodes between broadcast-based and unicast-based localization propagation in protocol stack. Results using Cooja simulator, demonstrate the trade-offs between unicast and broadcast transmission approaches, particularly in terms of network overhead, energy consumption and localization performance. For instance, with an antenna range of 20 meters, achieving a localization ratio of over 90% requires only 20% anchor density with broadcast transmission, whereas unicast transmission requires a 60% anchor density to achieve the same ratio. This demonstrates that broadcast localization can lead to approximately a 33% reduction in hardware costs, offering significant efficiency gains. These findings provide insights into optimal propagation techniques and highlight the advantages of broadcasting in resource-constrained WSN deployments.